Antenatal Care (ANC) Check-up Frequency Among Mothers in Salyan, Nepal - Bohara, Pradeep Kumar; Khanal, Tantrika Raj; Katuwal, Khadga Bahadur (Educational Journal, 2024)
This study analyses the experiences of antenatal care (ANC) use amongst the rural women in Salyan district, Nepal. A cross-sectional survey was conducted, and a systematic random sampling strategy was employed with mothers chosen by selecting every fifth case (sampling interval k=5) from a total of 1,610 eligible participants with children aged less than five years; data was analyzed through chi-square statistical procedure to identify the relationship between ANC attendance and demographic or household characteristics, which consisted of parity, maternal age, the level of education and occupation held by husband, as well as food security within the household. Findings exposed that the receipt of ANC depended on each of these aspects. Specifically, husband-related factors were notable: mothers whose husbands had secondary or higher schooling participated in almost all ANC visits (55 within 20) compared to Mothers whose husbands were non-educated. The effect of occupational status was also moderate. Still, in this case, 50 percent of the mothers whose husbands were in business services had attended four or above ANC visits compared to 10 percent of the mothers whose husbands worked in agriculture. Household economic stability also played an important role; women in food-secure homes were almost four times more likely to get four or above ANC visits compared to those on food insecurity (45 percent versus 15 percent). Lastly, another powerful variable was known as parity mother having 4 or more children was less likely to attend at least two ANC visits as compared to a mother having just one child (40 percent and 20 percent, respectively). All these findings show the importance of the involvement of male partners, economic security, and para-specific issues in determining the health-seeking behavior of women. The policymakers should consequently go beyond clinical-service provision to address systematic socioeconomic forms of subjection, food stabilization, and adaptation.